Characterization of Polyclonal Antibody Induced by Autoantibody TPO (Thyroidperoxidase) From Autoimmune Thyroid Disease (AITD) Serum with ELISA and Western Blotting - Maulidya Aulia Fiqriyana; Aulanni'am Aulanni'am; Anna Roosdiana (Chemistry Department, The University of Brawijaya, 2013)
Autoantibody TPO is a potential marker for early detection of autoimmune thyroid disease (AITD). Autoantibody TPO has a specifity and a sensitivity ranging from 82% to100% in comparison to other AITD serology markers. Concentration of autoantibody TPO in sera had a positive correlation with activities of chronic AITD. This research have been conducted to investigate the characteristic of polyclonal antibody TPO induced by autoantibody TPO from serum of AITD patients. The autoantibody TPO was isolated from serum of AITD patients and its band proteins was confirmed using western blotting, acquiring molecular weight of 51.81 kDa. The protein was induced to a rabbit (Oryctolagus cuniculus) and recognized as an antigen. Serum of rabbit produced polyclonal antibody which was characterized using ELISA and Western blotting. The result showed that autoantibody TPO isolated from serum of AITD patients was immunogenic, which induced the polyclonal antibody anti-TPO (anti-anti-TPO). It was found that the highest polyclonal antibody was obtained on 3rd serum bleeding with the absorbance of 0.3225 and a molecular weight of 51.81 kDa, which is able to specifically recognize autoantibody TPO. Keywords : Autoimmune thyroiditis, Autoantibody TPO, TPO, polyclonal antibody, ELISA, Western blotting